Analisis kemiskinan pada rumah tangga di Jawa Timur melalui pendekatan multidimensi dan moneter - Abdus Salam; Devanto Shasta Pratomo; Putu Mahardika Adi Saputra (Research Centre for Population, National Research and Innovation Agency (BRIN), 2021)
The first goal of the Sustainable Development Goals (SDGs) is to eradicate poverty in quantity and reduce poverty in various forms. The problem of poverty is often seen as a unidimensional problem. However, the measurement of poverty which uses only a monetary point of view is not enough to explain the deprivation experienced by the poor. Using the 2018 Indonesian National Socio-economic Survey (Susenas), this study analyzes the effect of household socioeconomic characteristics on multidimensional poverty status. Socioeconomic factors do not always have the same effect on multidimensional poverty or monetary poverty. The status of formal workers is only significant in monetary poverty. Regional topography has a strong influence on multidimensional poverty alone. Non-formal credit only affects monetary poverty and its direction is positive, whereas the distance to a public health centre (Puskesmas) only affects households that experience poverty and multidimensional poverty. Government efforts in reducing poverty may include re-promotion of family planning programs, expansion of Program Keluarga Harapan (PKH) services for households with disabilities, promotion of non-formal education programs in pursuit of education equivalency programmes (Kejar Paket A/B/C), as well as improvement of financial access to the community, especially to the poor through formal institutions, asphalt village road infrastructure, and improved health services in Puskesmas dan hospitalization facilities